EFEKTIVITAS PEMBINAAN DAN FUNGSI PEMASYARAKATAN PECANDU NARKOBA DI KOTA PALOPO - Sri Rahayu Amri (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2018)
Effectiveness can be interpreted as a process of achieving a goal that has been predetermined. A business or activity can be said to be effective if the business or activity has reached its goal. Coaching and correctional functions are held in the framework of the formation of correctional inmates in order to become fully human, aware of mistakes, improve themselves, and not repeat criminal acts so that they can be accepted again by the community, can actively play a role in development, and can live properly as good citizens and responsible. Drug addicts themselves are dependency users, who can not go through the day without taking drugs. This study aims to determine and analyze the effectiveness of coaching and correctional functions of drug addicts for correctional inmates, as well as factors that influence the effectiveness of coaching and correctional functions for drug addicts.This research is a description research with a juridical-empirical approach that examines the rules of positive law in order to get answers to existing problems by linking with facts or phenomena about drug addicts. The population in this study were all prisoners of drug addicts and functional officers at the Correctional Institution Class II in The Palopo City, while there were 50 people in the sample, where 25 drug addict inmates were assisted, and 20 correctional functional officers, and correctional hall officers 5 person.The output targets in this study are scientific publications in national journals with ISSN and unaccredited scientific journals. Other output targets other than those mentioned above are the creation of textbooks with ISSN Key word: Effectiveness, Guidance and Function of Corrections, Drug Addicts